Proteomic and phosphorylated proteomic landscape of injured lung in juvenile septic rats with therapeutic application of umbilical cord mesenchymal stem cells - Wang, Hongwu; Luo, Junlin; Li, Aijia; Su, Xing; Fang, Chuiqin; Xie, Lichun; Wu, Yi; Wen, Feiqiu; Liu, Yufeng; Wang, Tianyou; Zhong, Yong; Ma, Lian (Frontiers in Immunology, 2022)
Acute lung injury (ALI) is the most common complication of sepsis. Intravenous injection of HUMSCs can regulate the level of circulating endothelial cytokines and alleviate lung injury in juvenile septic rats. In this study, we performed proteomic and phosphorylated proteomic analysis of lung tissue of juvenile septic rats after Human Umbilical Cord Mesenchymal Stem Cells (HUMSCs) intervention for the first time, and screened the potential proteins and pathways of HUMSCs for therapeutic effect. The 4D proteome quantitative technique was used to quantitatively analyze the lung tissues of septic rats 24 hours (3 biological samples) and 24 hours after HUMSCs intervention (3 biological samples). A total of 213 proteins were identified as differentially expressed proteins, and 971 phosphorylation sites changed significantly. Based on the public database, we analyzed the functional enrichment of these proteins and phosphorylated proteins. In addition, Tenascin-C may be the key differential protein and ECM receptor interaction pathway may be the main signal pathway by using various algorithms to analyze the protein-protein interaction network. Phosphorylation analysis showed that tight junction pathway was closely related to immune inflammatory reaction, and EGFR interacted most, which may be the key differential phosphorylated protein. Finally, 123 conserved motifs of serine phosphorylation site (pS) and 17 conserved motifs of threonine (pT) phosphorylation sites were identified by motif analysis of phosphorylation sites. Results from proteomics and phosphorylated proteomics, the potential new therapeutic targets of HUMSCs in alleviating lung injury in juvenile septic rats were revealed.